Characteristic Analysis of Bump Foil Gas Bearing Under Multi-Physical Field Coupling - Daixing Lu; Zhengjun Zhu; Junjie Lu (Applied Sciences)
Due to their self-adaptability, low friction, low loss, and high-speed stability, bump foil aerodynamic journal bearings are widely used in high-speed rotating equipment such as turbomachinery and flywheel energy storage. In the process of high-speed operation, the heat generated leads to changes in air parameters (such as viscosity, density, etc.), thus affecting the overall performance of air bearings. In this paper, combined with the compressible Reynolds equation, a fluid–solid coupling model was established to analyze the steady-state characteristics and key influencing factors of bearings. Through the energy equation, the air viscosity–temperature effect was considered, and different boundary conditions were set. The internal temperature distribution of the air bearing and the influence of the temperature on the bearing characteristics were systematically analyzed. It was found that the bearing capacity increased when the temperature was considered. In a certain range, with the increase in ambient temperature, the increase in bearing capacity is reduced. This paper provides a theoretical design basis for the design of high-stability bearings and promotes the design of next-generation air bearings with higher speed, lower loss, and stronger adaptability, which has very important theoretical and engineering significance.